2021
DOI: 10.1186/s12872-021-02023-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between small dense low-density lipoprotein cholesterol with carotid plaque in Chinese individuals with abnormal carotid artery intima-media thickness

Abstract: Aim To investigate the relationship of small dense low-density lipoprotein cholesterol (sdLDL-C) to carotid artery intima-media thickness (CA-IMT) and carotid plaque (CAP) in Chinese general population, and to evaluate whether sdLDL-C could be an independent risk factor for individuals with subclinical atherosclerosis. Methods A total of 729 subjects were randomly collected from consecutive individuals from April 2019 to April 2020 for an annual he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Furthermore, high-density LDL particles have a higher affinity for proteinosan, which extends its stay on the wall and induces the development of AS. Moreover, the HDL-C particle size generally decreases with the increase in LDL-C/HDL-C, suggesting a blockade of HDL maturity, which may be responsible for the progression of AS [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, high-density LDL particles have a higher affinity for proteinosan, which extends its stay on the wall and induces the development of AS. Moreover, the HDL-C particle size generally decreases with the increase in LDL-C/HDL-C, suggesting a blockade of HDL maturity, which may be responsible for the progression of AS [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…AS mainly affects the intima of the large-and medium-sized arteries, characterized by lipid deposition, focal fibrosis, and the formation of atherosclerotic plaques, resulting in thickening, hardening, and lumen stenosis of the vessel wall, ultimately leading to ischemic changes in the corresponding organs. In recent years, some studies have confirmed that the ability of LDL-C to induce AS varies with different densities, and there is a stronger relationship between sdLDL-C and the stability of AS plaques (16,17). Ikezaki (18) followed 2,030 men and women [median age 59 years old, no cardiovascular disease (CVD) and not taking cholesterol-lowering drugs] for five years and performed univariate, multivariate regression and least squares analysis to examine the relationship between direct sdLDL-C and other lipoproteins with the progression of carotid intimal medial thickness (cIMT).…”
Section: Relationship Between Sdldl-c and Asmentioning
confidence: 97%